PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA PT. BANK NAGARI SUMATERA BARAT CABANG SIMPANG EMPAT PASAMAN BARAT - Nazaruddin Aziz; Rino Dwi Putra (JURNAL PUNDI, 2020)
This study aims to determine and analyze how much influence the Quality of Service (X) which consists of 5 research variables namely Tangible, Reliability, Responsiveness, Assurance and Emphaty and Customer Loyalty (Y) at PT. Bank Nagari, West Sumatra Branch Simpang Empat Pasaman Barat, using data collection methods in the form of a questionnaire of 100 respondents. In data analysis using validity, reliability, and classic assumption tests namely normality, multicollinearity and heteroscedasticity. The analytical method used is multiple linear regression analysis. As for testing the hypothesis that is the F test, the T test, the determinant coefficient R2 using SPSS tools. The results showed that the Tangible variable did not affect customer loyalty at PT. Bank Nagari Simpang Empat Pasaman Barat Branch, Reliability variable does not affect customer loyalty at PT. Bank Nagari Simpang Empat Pasaman Barat Branch, responsiveness variable does not affect customer loyalty at PT. Bank Nagari Simpang Empat Pasaman Barat Branch, Assurance variable does not affect customer loyalty at PT. Bank Nagari Simpang Empat Pasaman Barat Branch, Empathy variable does not affect customer loyalty at PT. Bank Nagari Simpang Empat West Pasaman Branch. Based on the results of linear regression testing found that the variable Service Quality consisting of Tangible, Reliability, Responsiveness, Assurance and Empathy does not have a significant effect on Customer Loyalty.